Non-neuronal cholinergic activity is potentiated in myasthenia gravis. Issue 1 (December 2017) - Han, Bin; Zhang, Chao; Liu, Shoufeng; Xia, Yiping; Sun, Hao; Gong, Zhongying; Simard, Alain; Liu, Qiang; Hao, Junwei
Abstract Background Non–neuronal acetylcholine (ACh) restricts autoimmune responses and attenuates inflammation by cholinergic anti-inflammation pathway. To date, the implication of ACh in myasthenia gravis (MG) remained unexplored. This study aimed to investigate the possible relationship between ACh levels, anti–muscle-specific tyrosine kinase (MuSK) antibody titers, main clinical features and outcomes of MG patients. Methods We successfully measured ACh levels in human peripheral blood mononuclear cells (PBMCs) from 125 MG patients and 50 matched healthy controls by using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). We assessed the quantitative MG (QMG) scores for each patient and titered anti-MuSK antibody. Results We found that PBMC-derived ACh level was significantly higher in MG patients, especially in patients of class III, IV-V, compared with that in controls (0.142 ± 0.108 vs. 0.075 ± 0.014 ng/million cells, p = 0.0003) according to the Myasthenia Gravis Foundation of America clinical classification. Importantly, we also found that ACh levels were positively correlated with QMG scores (r = 0.83, p < 0.0001) and anti–MuSK Ab levels (r = 0.85, p < 0.0001). Conclusions Our demonstration of elevated ACh levels in PBMCs of MG patients foreshadows potential new avenues for MG research and treatment.